ANALISIS PENERAPAN PAJAK PENGHASILAN FINAL PASAL 4 AYAT 2 PADA PERUSAHAAN JASA KONSTRUKSI PT. CONSPEC PERTAMA INDONESIA - Sri Setia Ningsih; Sari Yulianti; Erion Erion; Lestari Adhi Widyowati; Gunawan Raspatty (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The purpose of this research is to find out how the regulations of Tax Law Number 36 of 2008 concerning reporting and calculating final income tax on construction services at "PT Conspec Pertama Indonesia" are applied. Income from business entities that provide construction services is regulated by income tax article 4 paragraph 2 which is final. In this case, "PT Conspec Pertama Indonesia" is subject to a levy of 3%, which also applies to large and medium businesses. The methodology used in this research is qualitative, consisting of data collection, management, analysis and drawing conclusions. Final income tax on construction services is collected, managed and analyzed in this research. Findings were obtained from this analysis. The research results show that overall the implementation of the calculation, deduction, deposit and reporting system is in accordance with PMK regulation no. 153/PMK.03/2009 and PP no. 40 of 2009. In the event that the service user is not a tax withholder, he/she carries out the calculations and deductions himself. For the deposit system, e-billing has been used, and reporting via Periodic SPT has been attached along with proof of deductions. However, due to communication problems, there are still some differences in calculations and reporting delays. In the future, the tax and accounting department needs to be aware of this